The Pattern of mRNA Expression Is Changed in Sinoatrial Node from Goto-Kakizaki Type 2 Diabetic Rat Heart - F. C. Howarth; M. A. Qureshi; P. Jayaprakash; K. Parekh; M. Oz; H. Dobrzynski; T. E. Adrian (Journal of Diabetes Research)
Background. In vivo experiments in Goto-Kakizaki (GK) type 2 diabetic rats have demonstrated reductions in heart rate from a young age. The expression of genes encoding more than 70 proteins that are associated with the generation and conduction of electrical activity in the GK sinoatrial node (SAN) have been evaluated to further clarify the molecular basis of the low heart rate. Materials and Methods. Heart rate and expression of genes were evaluated with an extracellular electrode and real-time RT-PCR, respectively. Rats aged 12-13 months were employed in these experiments. Results. Isolated spontaneous heart rate was reduced in GK heart (161 ± 12 bpm) compared to controls (229 ± 11 bpm). There were many differences in expression of mRNA, and some of these differences were of particular interest. Compared to control SAN, expression of some genes were downregulated in GK-SAN: gap junction, Gja1 (Cx43), Gja5 (Cx40), Gjc1 (Cx45), and Gjd3 (Cx31.9); cell membrane transport, Trpc1 (TRPC1) and Trpc6 (TRPC6); hyperpolarization-activated cyclic nucleotide-gated channels, Hcn1 (HCN1) and Hcn4 (HCN4); calcium channels, Cacna1d (Cav1.3), Cacna1g (Cav3.1), Cacna1h (Cav3.2), Cacna2d1 (Cavα2δ1), Cacna2d3 (Cavα2δ3), and Cacng4 (Cavγ4); and potassium channels, Kcna2 (Kv1.2), Kcna4 (Kv1.4), Kcna5 (Kv1.5), Kcnb1 (Kv2.1), Kcnd3 (Kv4.3), Kcnj2 (Kir2.1), Kcnk1 (TWIK1), Kcnk5 (K2P5.1), Kcnk6 (TWIK2), and Kcnn2 (SK2) whilst others were upregulated in GK-SAN: Ryr2 (RYR2) and Nppb (BNP). Conclusions. This study provides new insight into the changing expression of genes in the sinoatrial node of diabetic heart.